A Second Las17 Monomeric Actin‐Binding Motif Functions in Arp2/3‐Dependent Actin Polymerization During Endocytosis. (24th February 2015) - Feliciano, Daniel; Tolsma, Thomas O.; Farrell, Kristen B.; Aradi, Al; Di Pietro, Santiago M.
Abstract During clathrin‐mediated endocytosis (CME), actin assembly provides force to drive vesicle internalization. Members of the Wiskott–Aldrich syndrome protein (WASP) family play a fundamental role stimulating actin assembly. WASP family proteins contain a WH2 motif that binds globular actin (G‐actin) and a central‐acidic motif that binds the Arp2/3 complex, thus promoting the formation of branched actin filaments. Yeast WASP (Las17) is the strongest of five factors promoting Arp2/3‐dependent actin polymerization during CME. It was suggested that this strong activity may be caused by a putative second G‐actin‐binding motif in Las17. Here, we describe the in vitro and in vivo characterization of such Las17 G‐actin‐binding motif (LGM) and its dependence on a group of conserved arginine residues. Using the yeast two‐hybrid system, GST‐pulldown, fluorescence polarization and pyrene‐actin polymerization assays, we show that LGM binds G‐actin and is necessary for normal Arp2/3‐mediated actin polymerization in vitro. Live‐cell fluorescence microscopy experiments demonstrate that LGM is required for normal dynamics of actin polymerization during CME. Further, LGM is necessary for normal dynamics of endocytic machinery components that are recruited at early, intermediate and late stages of endocytosis, as well as for optimal endocytosis of native CME cargo. Both in vitro and in vivo experiments show that LGM has relatively lower potency compared to the previously known Las17 G‐actin‐binding motif, WH2. These results establish a second G‐actin‐binding motif in Las17 and advance our knowledge on the mechanism of actin assembly during CME. <inline-graphic xlink:href="ark:/27927/pgjdnkzt04" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />